State Capture, Hybrid Regimes, and Security Sector Reform - Stojanović Gajić, Sonja; Pavlović, Dušan (Journal of Regional Security, 2021)
In this introduction into the special issue on state capture and security sector governance, we argue that state capture is a relevant concept that helps us understand the current autocratisation and the rise of hybrid regimes. We argue that the extraction of public resources via party patronage, privatization of public administration, judiciary, security institutions, and media are vital for influencing political competition. In the second part of the article, we argue that the concept of state capture brings added value to the understanding of security governance and transformations. We show why the parts or whole of security and justice institutions are the inevitable targets of state capture and what it means to understand the success of security sector reform (SSR). Finally, we examine a range of possible positions of the security sector within the captors and what it means for both the literature on state capture and civil-military relations.